DETERMINANTS OF EMPLOYEE TURNOVER INTENTION AT PT. FAJAR SURYA - Lukmansyah Rifai Amirudin; R. Madhakomala R. Madhakomala; Wibowo Wibowo (Jurnal EBI, 2023)
This study aims to develop a strategic model of the influence of career development, employee involvement, and employee engagement on the turnover intention at Fajar Surya. Quantitative methods are used in this study. The sample consists of 150 employees at the managerial level. The sample criteria in this study were permanent employees who had worked for at least 1 year. Data collection techniques by distributing questionnaires directly to all samples. Analysis of the data used is SEM-PLS. Empirical results show that career development and employee engagement have a negative and significant effect on turnover intention; with the greatest influence on career development variables. However, employee involvement has no significant effect on turnover intention. While career development has a positive and significant effect on employee engagement. However, employee involvement has no significant effect on employee engagement. Other results show that career development mediated by employee engagement has a negative and significant effect on turnover intention; However, employee involvement mediated by employee engagement has no significant effect on turnover intention. These empirical results show that the mediating role of employee engagement in career development can reduce employee intention to change jobs. This research resulted in a novelty of the turnover intention strategy model at Fajar Surya. Keywords: Turnover Intention; Career Development; Employee Involvement; Employee Engagement.